Solar hybrid systems : design and application - Aktas, Ahmet, 1987- (Academic Press, 2021)
Solar Hybrid Systems: Design and Application discusses the key power generation characteristics of solar systems and explores the growing need for hybrid systems. The authors use real-life examples to explain the disadvantages of solar systems without hybridization and to demonstrate the various applications hybrid solar systems can be used for, paying special attention to its integration with energy storage systems. The book also discusses the impact of hybridization and how this can improve power generation quality along with investigating novel and advanced hybrid solar systems. This is a useful reference for engineers and researchers involved in both the development and application of hybrid solar systems, and features topics such as solutions for the intermittence of renewable energy sources; on-gird and off-grid solar hybrid systems; the simulation, design and application of hybrid solar systems; the role of energy storage systems in solar hybrid applications; and the future of electric vehicles using solar hybrid systems.